Evaluation of the growth performance of fishes in industrial waste fed ponds under Rajshahi City Corporation (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Growth performance of fishes was evaluated for a period of six months (May to October, 2007) in industrial waste fed ponds located at Rajshahi City under three different treatments of species variation namely Tl (Labeo rohita, Catla catla, Cirrhinus mrigala, Hypophthalmichthys molitrix, Cyprinus carpio) in non waste pond, T2 (L. rohita, C. catla, C. mrigala, H. molitrix, C. carpio, Labeo bata) in industrial waste fed pond and T3 (L. rohita, C. catla, C. mrigala, H. molitrix, C. carpio, L. bata, Oreochromis nilotica) in waste fed pond. All the treatments were replicated twice. Stocking density 14,000 individuals/ha was same for all the treatments. The average initial weight of fish was 28.9g. Treatments had no significant effect on the mean SGR and survival rate of fishes except C. carpio. Mean SGR (%, bwd-1), weight gain (g), final weight (g) and survival rate (%) varied from 1.14±0.26 (T2) to 1.67±0.44 (T1), 34.00±2.81 (T2), to 114.22±12.37 (T1), 235.75±2.59 (T3) to 752.50±4.50 (T1), 60.50±4.50 (T3) to 82.50±2.50% (T2), respectively. Total fish yield (Kg/ha) significantly (P